Analisis Faktor Determinan kegagalan pemberian ASI eksklusif di Kampung Pasirido Manokwari - Yayuk Nuryanti; Waode Suriani (Jurusan Keperawatan Poltekkes Kemenkes Sorong, 2018)
Mother's milk (ASI) is the best food for babies, especially babies from 0-6 months called exclusive breastfeeding. ASI fulfills nutritional needs, has immune substances to protect babies from the dangers of infectious diseases, hygienic, always available at all times and the temperature is right. Some mothers in the village of Pasirido do not provide ASI exclusively for various reasons.The purpose of the study: to analyze the determinant factors of the failure of exclusive breastfeeding in the village of Pasirido. Study design: using correlation research. Population and sample: population of all mothers who have children aged 6-12 months. The sampling technique used was a total sample of 30 respondents. Tools: Data were collected using a questionnaire, data were analyzed univariately by percentage formula and bivariate with chi square. The results of the study were generally obtained that there was no failure of exclusive breastfeeding in Pasirido village. The knowledge factor chi square test results obtained p = 0.18 and attitudes p = 0.09. The value of these two factors is p> 0.05, so it is concluded that there is no relationship between knowledge and attitude towards the failure of exclusive breastfeeding in the village of Pasirido. Suggestion: health education about maternal and child health is carried out continuously and scheduled with different material. New mothers immediately give exclusive breastfeeding